The Development of ‘CATRA’ Android-Based Learning Module with Gamification Approach for Students: A Research and Development on Learning Media - Jiny Dharma Ditha; Susanto Susanto; Hendri Ardianto; Vike Aprilianin Marwintaria Saputri; Dittha Winyana Putra; Candra Kusuma (Universitas Sebelas Maret, 2024)
CATRA learning media is an Android-based learning module with a gamification approach. This study is motivated by the dominance of conventional methods in Senior High Schools, which shows the need for an innovative approach to learning. CATRA is designed as a multidimensional projection instrument to present the Four Noble Truths (Cattari Arya Saccani) material to create a more interactive and motivating learning environment. The methodology applied is research and development (R&D), with data collection procedures including observation, interviews, literature studies, and validation. The validation results from media experts, material experts, and Buddhist religious education teachers showed a very high level of feasibility, with a total score of 334, an average of 4.4, and a percentage of 88%. Based on these parameters, CATRA is classified as